Analisis Kepemimpinan Perempuan Muslim dalam Konteks Kontemporer - Mufarikhin, Mufarikhin; Dewi, Siti Malaiha (POLITEA, 2021)
Women's leadership has been a controversial issue in the contemporary history of several Muslim societies. Meanwhile, in relation to this, some scholars have permitted it as a form of social necessity in a modern context, most Muslim scholars have also refused because of its effect which is considered to be debilitating. Examples of women's leadership in general and as heads of Muslim states can be found in the context of the success of Benazir Bhutto in Pakistan, Khalida Zia and Sheikh Hasina in Bangladesh, Megawati Sukarnoputri in Indonesia, Atifete Jahjaga in Kosovo, Roza Otunbayeva in Kyrgyzstan, and Mame Madior Boye in Senegal. This issue is debatable because there is no clear direction regarding the leadership of the state and the high position of government which makes the problem divisive and full of conflict. Given the context, there is a need to analyze Muslim leadership in a contemporary context. This paper discusses the concept, brief history, the importance of women's leadership and analyzes the views of Islamic scholars within the scope of contemporary Islamic thought, which are based on the textual arguments of the Qur'an and Sunnah of Muslim scholars. This paper concludes that although a small portion of the entire Muslim spectrum tries to justify allowing women's leadership to develop social, economic and political perspectives, many Muslim scholars view it as a violation of God's commandments and, therefore, strictly preventing the appointment of women as both heads of state. high government officials.